2007
DOI: 10.1016/j.lfs.2007.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The cholinergic system is involved in regulation of the development of the hematopoietic system

Abstract: Gene expression profiling demonstrated that components of the cholinergic system, including choline acetyltransferase, acetylcholinesterase and nicotinic acetylcholine receptors (nAChRs), are expressed in embryonic stem cells and differentiating embryoid bodies (EBs). Triggering of nAChRs expressed in EBs by nicotine resulted in activation of MAPK and shifts of spontaneous differentiation toward hemangioblast. In vivo, non-neural nAChRs are detected early during development in fetal sites of hematopoiesis. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 25 publications
1
24
0
2
Order By: Relevance
“…38 In an older report, cholinergic signaling during early megakaryopoiesis was described. 39 In our study, we found expression of the nAChR␣7 subunits in cells of the megakaryocytic lineage. This could be part of a functional cholinergic system involved in the regulation of megakaryopoiesis and thrombopoiesis.…”
Section: Discussionsupporting
confidence: 54%
“…38 In an older report, cholinergic signaling during early megakaryopoiesis was described. 39 In our study, we found expression of the nAChR␣7 subunits in cells of the megakaryocytic lineage. This could be part of a functional cholinergic system involved in the regulation of megakaryopoiesis and thrombopoiesis.…”
Section: Discussionsupporting
confidence: 54%
“…These parameters might also be responsible for the highly variable expression pattern of the individual donors. The presence of cholinergic receptors is confirmed in embryonic stem cells where mRNA of all nAChR α-and β-subunits [19] as well as all subtypes of mAChR was determined [9]. Functions of AChR on embryonic stem cells are (a) mobilization of intracellular Ca 2+ , and (b) an increase in viability without changes in proliferation [20].…”
Section: Discussionmentioning
confidence: 94%
“…This receptor has been found in many non-excitable cells and seems to play a universal signaling role due to its high permeability to Ca 2+ [3]. Previously we found that ␣7 nAChRs were present in the blood cells starting from the very early precursors [29]; they supported the lymphocyte survival in the course of differentiation, as well as propagation of mature lymphocytes in the spleens of mice treated with nicotine [12]. In contrast, either the absence of ␣7 nAChRs in ␣7 knockout mice [30] or their pharmacological blockade in the wild-type animals favored B lymphocyte activation in vitro and the antibody production in vivo [31].…”
Section: Discussionmentioning
confidence: 99%